Designing a Coastal and Mangrove Resort at Kurnia Beach Kota Pari Village - Melly Andriana; Fariz Harindra Syam; Syahna Dwi Ardianti (Journal of Information Technology, computer science and Electrical Engineering, 2024)
The development of a coastal and mangrove resort at Pantai Kurnia in Desa Kota Pari presents a unique opportunity to leverage local natural resources and promote sustainable tourism. This article explores the design principles of the resort, emphasizing the integration of eco-friendly architecture, conservation of mangrove ecosystems, and community involvement. By adopting a participatory approach, the project aims to enhance local economic development while preserving the environment. The findings suggest that sustainable design can yield both ecological and economic benefits for the community.